REHABILITATION PLAN FOR ANKLE SPRAINS IN SOCCER PLAYERS (Fiep Bulletin - online, 2025)
Introduction: The second degree ankle sprain represents one of the most frequent injuries in football, with a significant impact on the player's performance and their continuity in sports practice. Athletes' perception of exercise plans for recovery is crucial to designing effective rehabilitation. Objective: The objective of this work is to describe the Perception of the application of a plan for the rehabilitation of grade 2 ankle sprains in non-professional soccer players in the age range of 18 to 25 years from a physiotherapy rehabilitation center in Asunción Paraguay. Methods: A plan with exercises for rehabilitation was applied. The mini BESTest test was used to evaluate balance and the visual analogue scale to measure pain. Data on the perception of the plan were collected through a questionnaire. Results: Most participants experienced a reduction in pain and improvement in ankle balance. The evaluation of the physical exercise plan was mostly positive, highlighting aspects such as structure, professional support and physical improvement. The results showed improvements in balance and reduction in pain, with a positive evaluation of the plan by the participants. Conclusion: The non-professional soccer players evaluated favorably perceived the effectiveness of the physical exercise plan in their rehabilitation. Close collaboration between Physical Education teachers and physiotherapists is recommended, as well as the implementation of an interdisciplinary approach in the formation of professional teams in the field of rehabilitation and training of non-professional footballers.
Keywords: Grade 2 ankle sprain; pain; balance; assessment of the physical exercise plan